Neo-Romanticism in the works of modern Belarusian authors: problems of receptive aesthetics (by the example of V. Karatkevich, L. Rublevska, V. Shnip) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article through the prism of neoromantic works of art of V. Karatkevich, L. Rublevskaya, V. Shnip are analyzed. The interaction of the reader and the author, the text and intertext disclosed in relation to certain ways to express the essence of the reception. The poetics of works of art is considered at detailed studying of processes of perception, understanding and text interpretation. Associativity affect "the horizon of expectations" of the reader and his perception of the artwork.
Keywords: neoromantic; reception aesthetics